Managing Risks in a Manufacturing Environment : A Perspective from Reason’s Accident Causation Model - syed mohamed, muhammad syafiq; ideris, harizah (CENTRE OF PROMOTING RESEARCH EXCELLENCE (CPRE), 2012)

(untitled)
Risk management in manufacturing industry can be an arduous task for employers. Statistics have shown that thousands of lives have been claimed by industrial accidents worldwide. In this study, a hazard identification and risk assessment exercise was conducted for lathe and welding machines in a manufacturing laboratory located in a public university in Malaysia. The hazards were then further analyzed with James Reason Swiss Cheese model for accident causation in order to identify probable latent causes of accidents. Hazards for both welding and lathe machines were quantified in order to determine their risk levels. Probable latent causes for accidents for both lathe and welding machines were identified as lack of resources for individual monitoring, lack of safety culture, and lack of resources for cleaning maintenance. Further potential actions were discussed in this paper.